2017
DOI: 10.1002/hep4.1121
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of liver fibrosis reveals a nonlinear association with fibrosis stage in nonalcoholic fatty liver disease

Abstract: Accurate staging of liver fibrosis is crucial to guide therapeutic decisions for patients with nonalcoholic fatty liver disease (NAFLD). Digital image analysis has emerged as a promising tool for quantitative assessment of fibrosis in chronic liver diseases. We sought to determine the relationship of histologic fibrosis stage with fiber amounts quantified in liver biopsy specimens for the better understanding of NAFLD progression. We measured area ratios of collagen and elastin fibers in Elastica van Gieson‐st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 50 publications
4
43
0
Order By: Relevance
“…In contrast, development of fibrosis in viral hepatitis is initially centred around the portal tract with subsequent rapid expansion towards the centrilobular vein . Existing studies on CPA measurement in NAFLD did not test higher magnifications and importantly did not validate CPA against clinical outcomes . We therefore tested different magnifications for digital analysis and CPA measurement in order to accurately quantify the presence of fine pericellular fibrosis that could be missed at a standard magnification.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, development of fibrosis in viral hepatitis is initially centred around the portal tract with subsequent rapid expansion towards the centrilobular vein . Existing studies on CPA measurement in NAFLD did not test higher magnifications and importantly did not validate CPA against clinical outcomes . We therefore tested different magnifications for digital analysis and CPA measurement in order to accurately quantify the presence of fine pericellular fibrosis that could be missed at a standard magnification.…”
Section: Discussionmentioning
confidence: 99%
“…The application of computer‐assisted quantitative analysis revealed that the pattern of liver fibrosis progression in NAFLD was different from that of chronic HCV infection: a striking difference was observed in fiber accumulation between Brunt's fibrosis stages F3 and F4 in NAFLD, in contrast to the somewhat linear association observed in chronic HCV infection . Moreover, the ranges of collagen and elastin levels in F4 stage NAFLD were larger than for stages F1–3 . Classical pathological staging systems have no stage beyond F4; however, it appears that fibrosis progresses and parenchymal remodeling continues even within the final fibrotic stage F4 .…”
Section: Assessment Of Liver Fibrosismentioning
confidence: 98%
“…20 Furthermore, advanced fibrosis is associated with an increased risk of mortality in NAFLD. 22 The application of computer-assisted quantitative analysis revealed that the pattern of liver fibrosis progression in NAFLD was different from that of chronic HCV infection: a striking difference was observed in fiber accumulation between Brunt's fibrosis stages F3 and F4 in NAFLD, 23 in contrast to the somewhat linear association observed in chronic HCV infection. 24 Moreover, the ranges of collagen and elastin levels in F4 stage NAFLD were larger than for stages F1-3.…”
Section: Liver Fibrosis In Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%
“…Non-alcoholic steatohepatitis (NASH) is characterized by steatosis and resultant inflammation causing progressive liver injury and fibrosis in patients where no alcoholic, genetic, metabolic, or medication-based causes for hepatitis have been identified (Masugi et al, 2017). Progressive NASH can lead to cirrhosis which causes a markedly increased risk of hepatocellular carcinoma (HCC) and can require transplantation in end stage disease (causing a major human and financial impact on the healthcare system).…”
Section: Synthetic Trichrome Staining Of Liver Tissuementioning
confidence: 99%
“…Non-alcoholic steatohepatitis (NASH) is characterized by steatosis and chronic inflammation causing progressive liver injury and fibrosis in patients where no alcoholic, genetic, metabolic, or medication-based causes for hepatitis have been identified (Masugi et al, 2017). Progressive NASH can lead to cirrhosis with morbidities including ascites, sepsis, coagulopathies, and nutritional deficiencies, and a markedly increased risk of hepatocellular carcinoma (HCC).…”
Section: Synthetic Trichrome Staining Of Liver Tissuementioning
confidence: 99%